Luther on marriage, adultery, and its punishment: A brief comparison with Calvin’s thoughts - Magyar, Balázs Dávid (Stellenbosch Theological Journal, 2023)
The early period of the time of the Reformation was full of social, economic, and political problems reaching the circumstances of status confessionis. It is beyond dispute that the two high esteemed reformers, Luther and Calvin paid strong theological and ethical attention to the evaluation of the several topics of sexuality. Pursuing this “holy project” they were struggling for a more sacred marital and family life. However, as the reformers were trying to commit everything to prevent sexual sins/crimes, there still were so many cases when they were called to discuss in detail what the adequate punishments of adultery would be.